2000
DOI: 10.1021/bi000319w
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Plasticity in Protein Tyrosine Phosphatase 1B Substrate Recognition,

Abstract: Protein tyrosine phosphatase 1B (PTP1B) displays a preference for peptides containing acidic as well as aromatic/aliphatic residues immediately NH(2)-terminal to phosphotyrosine. The structure of PTP1B bound with DADEpYL-NH(2) (EGFR(988)(-)(993)) offers a structural explanation for PTP1B's preference for acidic residues [Jia, Z., Barford, D., Flint, A. J., and Tonks, N. K. (1995) Science 268, 1754-1758]. We report here the crystal structures of PTP1B in complex with Ac-ELEFpYMDYE-NH(2) (PTP1B.Con) and Ac-DAD(B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
112
2
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 51 publications
19
112
2
1
Order By: Relevance
“…Structural studies of human Cdc25A (44) and Cdc25B (45) phosphatases revealed enzymes with shallow, solvent-exposed active sites with relatively few protein functional groups in positions where they would be likely to participate in catalysis. This is in contrast to other PTPases such as Yersinia PTPase (54), PTP1B (55)(56)(57), the low molecular weight PTPase (58,59) and VHR (60), which have surface loops that close around the substrate, bringing a variety of functional groups, including the general acid, into the active site and virtually surrounding the substrate. In Cdc25, the only residues that appear able to participate directly in catalysis are located in the phosphate-binding loop itself, corresponding to the CX 5 R motif (residues Cys 430 -Arg 436 in Cdc25A).…”
Section: Resultsmentioning
confidence: 76%
“…Structural studies of human Cdc25A (44) and Cdc25B (45) phosphatases revealed enzymes with shallow, solvent-exposed active sites with relatively few protein functional groups in positions where they would be likely to participate in catalysis. This is in contrast to other PTPases such as Yersinia PTPase (54), PTP1B (55)(56)(57), the low molecular weight PTPase (58,59) and VHR (60), which have surface loops that close around the substrate, bringing a variety of functional groups, including the general acid, into the active site and virtually surrounding the substrate. In Cdc25, the only residues that appear able to participate directly in catalysis are located in the phosphate-binding loop itself, corresponding to the CX 5 R motif (residues Cys 430 -Arg 436 in Cdc25A).…”
Section: Resultsmentioning
confidence: 76%
“…deviation 1.1 Å). Unlike PTP1B, where peptide substrate binding induces the closure of the WPD-loop (encompassing residues 191-199 in Lyp) (29,31), the WPD-loop in both of the Lyp/C227S-peptide complexes exists in the open conformation.…”
Section: 48)mentioning
confidence: 99%
“…2D). Although PTP1B has been shown to dephosphorylate a wide variety of synthetic peptides in vitro (18), it displayed no measurable activity against the H2A.X phospho-Tyr-142 peptide. Overall, these data suggest that EYA2 and EYA3 have the potential to exhibit selectivity in the dephosphorylation of phosphoTyr-142 of histone H2AX.…”
mentioning
confidence: 99%